Interview Mode and Measurement of Sexual Behaviors: Methodological Issues - Gribble, James N. (1999)
Studies of sexual and other sensitive behaviors are often fraught with a variety of reporting biases. When IAQs are used to collect data, respondents may underreport certain sensitive behaviors and overreport normative behaviors. SAQs can also pose problems: requiring that respondents be literate and able to follow skip patterns. In recent years, the development of computerized technologies--audio-CASI and T-ACASI--have begun to overcome some of the limitations of IAQs and SAQs. By providing a more private mode for data collection and standardized delivery of all questions, as well as automated skip patterns and range checks, audio-CASI and T-ACASI have been tested in a number of studies and found to be an effective way of reducing response bias, and thus, contributing to a better understanding of the prevalence and patterns of sexual and other sensitive behaviors.